BENTUK, FUNGSI DAN MAKNA ORNAMEN SUNTIANG MARAPULAI DI INDERAPURA PESISIR SELATAN - FADILLA YODINDA, Dr. Yahya, M.Pd., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this research is to gain an overview of form, function and meaning of ornament suntiang marapulai on the southern coast of Indrapura. This research is a descriptive qualitative belongs. The subject of research is the Chair of the indigenous peoples and citizens of Indrapura. The technique of collecting data through observation, interview techniques, engineering documentation. Research data includes some of the following, 1) to know the shape of the ornament of the suntiang marapulai (the groom) on the South coast of Indrapura. 2) to find out the function of ornament of the suntiang marapulai (the groom) South coast of Indrapura. 3) to find out the meaning of the ornament of the suntiang marapulai (the groom) on the South coast of Indrapura.Keywords: Form, Function, Meaning and Descriptive Qualitative